Hair cell apoptosis and deafness in Tmc1 mutations - Maryline Beurg; Dakota Elle Konrad; Robert Fettiplace (Proceedings of the National Academy of Sciences, 2025)
Transmembrane channel-like protein 1 (TMC1), a pore-forming component of the mechano-electrical transducer (MET) channel in cochlear outer hair cells, is subject to numerous mutations causing deafness and hair cell death. We studied mice harboring semidominant mutations Tmc1 p.T416K, p.M412K, and p.D569N, which all display functional MET channels at postnatal day (P)6 but become deaf by P21. Early signs of concomitant hair cell apoptosis were assayed in neonatal Tmc1 mutants by labeling with Calcein-acetomethyl ester (AM), MitoTracker, and Annexin V, the latter labeling scramblase externalization of phosphatidyl serine. Reduced labeling with Calcein-AM was correlated with reduced MitoTracker, the targeting of mitochondria being confirmed with the uncoupling agent carbonylcyanide p -trifluoromethoxyphenylhydrazone, and use of MitoLight to monitor mitochondrial membrane potential. These markers demonstrated mitochondrial dysfunction in Tmc1 mutants, even at P6 when MET currents were still present. Acoustic brainstem responses established that Tmc1 p.D569N and Tmc1 p.M412K mice were deaf by P15 and Tmc1 p.T416K by P21. Two methods of blocking the stereociliary PMCA2 Ca 2+ pump both elicited scramblase activity, suggesting that apoptosis is promoted by elevation of hair bundle [Ca 2+ ]. Reduced PMCA2 density was found in the stereocilia of Tmc1 mutants and was correlated with a decrease in MET channel Ca 2+ permeability. Cre-Lox excision of the mutant M412K exon at P1 fully preserved hearing across all frequencies by P19 and promoted recovery to wild type of PMCA2 density. These results demonstrate that hair cells in Tmc1 mutants have embarked on apoptosis at P6 and argue for connections between stereociliary PMCA2 density, hair cell apoptosis, and deafness.